2009
DOI: 10.3109/09638280903186335
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of stroke survivors – A validation of the ICF core set for stroke in Sweden

Abstract: Purpose. To validate the body functions and activities and participation part of the extended International Classification of Functioning, Disability, and Health (ICF) core set for stroke with a Swedish population in the first 3 months post-stroke. Method. At 6 weeks and at 3 months post-stroke, stroke survivors were evaluated by 59 ICF categories of body functions, 59 categories of activities and participation from the stroke ICF core set (extended version).Results. The study sample included 99 stroke survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 45 publications
5
48
1
2
Order By: Relevance
“…The most frequent environmental factor intervention was e120 products and technology for personal mobility (5.7%). This result differs from a similar study which found the most frequent environmental facilitator was e540 social security systems, services and policies (95.5%) [13]. These differences may reflect the unique health and social systems of the country where the study was conducted.…”
Section: Environmental Factor Categoriescontrasting
confidence: 56%
See 3 more Smart Citations
“…The most frequent environmental factor intervention was e120 products and technology for personal mobility (5.7%). This result differs from a similar study which found the most frequent environmental facilitator was e540 social security systems, services and policies (95.5%) [13]. These differences may reflect the unique health and social systems of the country where the study was conducted.…”
Section: Environmental Factor Categoriescontrasting
confidence: 56%
“…A study of 99 Swedish people with stroke found although basic interpersonal problems were not significant at 6 weeks and 3 months post stroke, handling stress and other psychological demands was significant at both time points [13]. The need for interventions for emotional concerns is also supported by Allen et al [29] who found that at one year post stroke 31.7% of patients were classified as depressed.…”
Section: Activities and Participationmentioning
confidence: 53%
See 2 more Smart Citations
“…Detailed information about participants' problems and facilitators during the first 3 months was given in 2 previous articles. 29,30 HRQoL and consequences for participants are presented in Table 2.…”
Section: Results Participantsmentioning
confidence: 99%